2015
DOI: 10.1073/pnas.1508821112
|View full text |Cite
|
Sign up to set email alerts
|

Next-generation libraries for robust RNA interference-based genome-wide screens

Abstract: Genetic screening based on loss-of-function phenotypes is a powerful discovery tool in biology. Although the recent development of clustered regularly interspaced short palindromic repeats (CRISPR)-based screening approaches in mammalian cell culture has enormous potential, RNA interference (RNAi)-based screening remains the method of choice in several biological contexts. We previously demonstrated that ultracomplex pooled short-hairpin RNA (shRNA) libraries can largely overcome the problem of RNAi off-target… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
91
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(91 citation statements)
references
References 29 publications
(40 reference statements)
0
91
0
Order By: Relevance
“…To find the ideal shRNA or sgRNA coverage and design, multiple studies have performed small-scale pooled screens with very high coverage of shRNAs or sgRNAs per gene (29,69,80,81). These studies each identified high-confidence hits and then computationally subdivided their libraries to (i) discover the number of sgRNAs required to distinguish true hits from the background and (ii) define rules that make more effective shRNAs and sgRNAs.…”
Section: Crispri Versus Previous Repression Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To find the ideal shRNA or sgRNA coverage and design, multiple studies have performed small-scale pooled screens with very high coverage of shRNAs or sgRNAs per gene (29,69,80,81). These studies each identified high-confidence hits and then computationally subdivided their libraries to (i) discover the number of sgRNAs required to distinguish true hits from the background and (ii) define rules that make more effective shRNAs and sgRNAs.…”
Section: Crispri Versus Previous Repression Methodsmentioning
confidence: 99%
“…These studies each identified high-confidence hits and then computationally subdivided their libraries to (i) discover the number of sgRNAs required to distinguish true hits from the background and (ii) define rules that make more effective shRNAs and sgRNAs. Thus, bioinformatic modeling and iterative analysis and testing large pools of sgRNAs have resulted in significant improvements in both RNAi and CRISPRi (29,69). It is now possible to use a library with 10 shRNAs or 10 sgRNAs per gene to produce robust results in a screen, although both RNAi and CRISPRi will no doubt benefit from further refinement in the future.…”
Section: Crispri Versus Previous Repression Methodsmentioning
confidence: 99%
“…For example, CRISPRi modulates transcription at the TSSs of endogenous genes; therefore, it is difficult to target specific splice isoforms. By contrast, RNAi can be targeted to specific mature transcripts 74 . Therefore, the use of CRISPRi and RNAi in conjunction may hold the potential for more complete analysis of gene function.…”
Section: Crispr–dcas9 Applicationsmentioning
confidence: 99%
“…CRISPR-mediated repression (CRISPRi) and activation (CRISPRa) has been demonstrated as robust tools for functional genome screening in gene expression modulation. CRISPRi has been efficiently exploited to inhibit the transcription of target genes in E. coli and mammalian cells when dCas9 is recruited to transcriptional inhibitory domain 22 , whereas to activate the expression of target endogenous genes when dCas9 is tethered to a transcriptional activator domain 31,32 . Genome-scale CRISPRi/a libraries have been successfully employed in identification of mediators for cellular sensitivity to a cholera-diptheria fusion toxin, as well as essential genes for proliferation, differentiation and tumor suppression.…”
Section: Cas9 In Cancer Research Diagnosis and Therapeuticsmentioning
confidence: 99%
“…Additionally, CRISPRa helps in identification of a novel gene with its gainof-function properties. dCas9 when complexes with sgRNA has shown to successful in simultaneous activation of multiple genes, up regulation of long noncoding RNA transcripts and identifying genes conferring resistance to a BRAF inhibitor in melanoma 32 signifying the versatility of this system in discovering crucial genes in various biological processes.…”
Section: Cas9 In Cancer Research Diagnosis and Therapeuticsmentioning
confidence: 99%